2009
DOI: 10.1103/physrevb.79.092410
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant-spin-glass state inNi2Mn1.36Sn0.64shape-memory alloy

Abstract: The ground state properties of the ferromagnetic shape memory alloy of nominal composition Ni2Mn1.36Sn0.64 have been studied by dc magnetization and ac susceptibility measurements. Like few other Ni-Mn based alloys, this sample exhibits exchange bias phenomenon. The observed exchange bias pinning was found to originate right from the temperature where a step-like anomaly is present in the zero-field-cooled magnetization data. The ac susceptibility study indicates the onset of spin glass freezing near this step… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(89 citation statements)
references
References 26 publications
7
81
0
Order By: Relevance
“…Strong frequency dependence of ac susceptibility results clearly demonstrated SG-like behaviour close to EB blocking temperature, above which EB effect was vanished. The EB effect involved with RSG state at low temperature was reported in Ni 50 Mn 34 Sn 16 where RSG state was confirmed based on frequency dependence of ac susceptibility results [165]. The ac susceptibility study indicated an onset of SG freezing near step-like anomaly with a clear frequency shift and RSG was envisaged in terms of coexisting FM and glassy magnetic phases at low temperature at least in field-cooled state.…”
Section: Ni-mn-sn Alloysmentioning
confidence: 82%
“…Strong frequency dependence of ac susceptibility results clearly demonstrated SG-like behaviour close to EB blocking temperature, above which EB effect was vanished. The EB effect involved with RSG state at low temperature was reported in Ni 50 Mn 34 Sn 16 where RSG state was confirmed based on frequency dependence of ac susceptibility results [165]. The ac susceptibility study indicated an onset of SG freezing near step-like anomaly with a clear frequency shift and RSG was envisaged in terms of coexisting FM and glassy magnetic phases at low temperature at least in field-cooled state.…”
Section: Ni-mn-sn Alloysmentioning
confidence: 82%
“…The step-like anomaly in ZFC (marked as T*) is due to the drop in magnetization arising from the competition between ferromagnetic and antiferromagnetic interaction. The exchange bias phenomenon is reported below T* temperature 43,44 . The competing magnetic interactions lead to spin freezing and re-entrant spin glass-like behaviour at the low-temperature martensitic phase 43 .…”
Section: Magnetic Behaviourmentioning
confidence: 99%
“…They provide fascinating electronic and magnetic properties, which include phase coexistence, metastability, field induced reverse transition, glassy magnetic phase, magnetic exchange anisotropy, kinetically arrested state, inverse magnetocaloric effect etc. [6][7][8][9][10][11]. It has been observed that the magnetic, electronic and structural properties of these alloys are very closely interlinked.…”
Section: Introductionmentioning
confidence: 97%